Karakteristik Demografi, Letak Kelainan Anatomi, serta Gambaran Histopatologi Responden dengan Diagnosis Klinis Gastritis - Shalmont, Grace; Wijaya, Dean Ascha; Kurniawan, Joshua; Firmansyah, Yohanes (Universitas Malahayati, 2023)
ABSTRACT Gastritis is often used to describe clinical symptoms related to upper abdominal complaints in patients. The diagnosis of gastritis is established by combining information resulting from endoscopy examination and histological findings. This cross-sectional study aims to examine the demographic and pathological profile of gastritis patients in one of the hospitals in Jakarta, selected based on total sampling criteria using medical record data from January 2020 to December 2022. The data is presented in descriptive form. Out of 43 respondents, the mean age is 47 years and the majority are male. The most common location of pathology is in the antral part of the stomach in 29 (67.4%) respondents, with the inflammation generally being mild in 30 (69.8%) respondents. No PMN cells, atrophy, or Helicobacter pylori bacterial infection were found in 42 (97.7%) respondents, and there was no evidence of intestinal metaplasia or dysplasia in any of the respondents. The conclusion of this study is that the most common location of pathology is in the antral section with generally mild infection with a predominance of Helicobacter pylori infection. Keywords: Endoscopy, Gastritis, Histopathology ABSTRAK Gastritis sering digunakan untuk menggambarkan gejala klinis yang berkaitan dengan keluhan pasien di perut bagian atas. Diagnosis gastritis ditegakkan setelah menggabungkan informasi yang dihasilkan dari pemeriksaan endoskopi dan temuan histologis. Penelitian potong lintang ini bertujuan melihat gambaran demografi dan patologi pasien gastritis di salah satu Rumah Sakit di Jakarta yang dipilih sesuai kriteria secara total sampling menggunakan data rekam medis periode Januari 2020 hingga Desember 2022. Data disajikan dalam bentuk deskriptif. Dari 43 responden, rerata usia adalah 47 tahun dan didominasi oleh laki-laki. Letak patologi paling sering terjadi pada bagian antral gaster pada 29 (67,4%) responden, dengan sebukan sel radang kronik umumnya sedang pada 30 (69,8%) responden, tidak ada sebukan sel PMN, atrofi kelenjar dan infeksi bakteri Helicobacter pylori pada 42 (97,7%) responden, serta tidak ditemukannya metaplasia intestinal dan displasia pada seluruh responden. Kesimpulan penelitian ini berupa lokasi patologi paling umum adalah pada bagian antral dengan infeksi umumnya ringan dengan dominasi infeksi Helicobacter pylori. Kata kunci: Endoskopi, Gastritis, Histopatologi